Criteria, Indices and Levels of Self-Realization of Students of Higher Educational Establishments in the Process of Spare Time Activity - Hutsol, Liudmyla (Pedagogical Discourse, 2016)
The article deals with the theoretical bases of preparing students for self-realization in the process of spare time activity. The theoretical approaches of scientists to the definition of the terms «criterion», «index», «level» and «readiness» have been generalized. The content of the motivational, cognitive, activity, reflexive and emotional-volitional components of readiness for self-realization has been revealed. The criteria (motivational, cognitive, activity, reflexive and emotional- volitional) have been determined and their indices for achievement of high results in increasing the level of the researched concept based on the essence of the structural components of self-realization have been proved. The levels of readiness of students to self-realization in the process of spare time activity have been given, taking into account their internal structure, namely: reproductive (low) level, which is characterized by the absence of sustainable desire to conduct self-realization, lack of interest in self-realization, lack of aspiration for the identification and disclosure of their capabilities: a student doesn’t realize the potential, the self-esteem is overestimated or underestimated, he or she does not show strong-willed efforts to realize himself or herself in spare time activity; a student is characterized by the tendency to act only under someone’s leadership; constructive (average) can be characterized by: the presence of desire to exercise self-realization, presence of the interest in self-realization, a student does not fully disclose his or her abilities and capacities, cannot independently use the potential, does not enough show volitional efforts to self-realization in spare time activity; creative (high) is characterized by: the steady desire to exercise self-realization, existing risen demand and interest in self-realization, a student can realize the potential, perceive the commitment to the identification and disclosure of the capabilities and abilities, he or she is able to use own potential, can realize himself or herself and the subject knowledge in a range of spare time classes, sets goals and shows volitional effort in the achievements of spare time activity. Key words: personality, student, components, criteria, indices, levels, self-realization, spare time activity.